Enhancement of hMSC In Vitro Proliferation by Surface Immobilization of a Heparin-Binding Peptide - Cimino, M (2023)
The use of human Mesenchymal Stem Cells (hMSC) as therapeutic agents for advanced clinical therapies relies on their in vitro expansion. Over the last years, several efforts have been made to optimize hMSC culture protocols, namely by mimicking the cell physiological microenvironment, which strongly relies on signals provided by the extracellular matrix (ECM). ECM glycosaminoglycans, such as heparan-sulfate, sequester adhesive proteins and soluble growth factors at the cell membrane, orchestrating signaling pathways that control cell proliferation. Surfaces exposing the synthetic polypeptide poly(L-lysine, L-leucine) (pKL) have previously been shown to bind heparin from human plasma in a selective and concentration-dependent manner. To evaluate its effect on hMSC expansion, pKL was immobilized onto self-assembled monolayers (SAMs). The pKL-SAMs were able to bind heparin, fibronectin and other serum proteins, as demonstrated by quartz crystal microbalance with dissipation (QCM-D) studies. hMSC adhesion and proliferation were significantly increased in pKL-SAMs compared to controls, most probably related to increased heparin and fibronectin binding to pKL surfaces. This proof-of-concept study highlights the potential of pKL surfaces to improve hMSC in vitro expansion possible through selective heparin/serum protein binding at the cell-material interface.